Studi Kandungan Logam Berat Timbal (Pb) pada Ikan, Krustasea dan Moluska di Pantai Utara Bangkalan, Madura [Study Of Heavy Metal Lead (Pb) In Fish, Crustaceans And Mollusks At The Northern Coast Of Bangkalan, Madura] - M. Arief; Reza Nurhuda; Boedi Setya Rahardja (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Currently a variety of activities and industrial activity at Bangkalan increas the presence Suramadu bridge. It will provide an increasingly severe impact on the coastal environment (Purnomo, 2007). In 2010 it has been observed that the heavy metal content of lead at marine district Bangkalan average reached 0.083 mg/l. The value has exceeded the maximum threshold of Pb in water that can be used fishing activity is 0.008 mg/l so that the marine district. Bangkalan classified as polluted. The purpose of this study was to determine levels of heavy metal lead (Pb) in fish, crustaceans and mollusks in the northern Bangkalan beaches. This research activity covers observations in the field and analysis laboratory in April-May 2013. Water and sediment sampling conducted at three locations in the waters of the North Coast Klampis, Sepulu and Tanjung Bumi, while samples of fish, crustaceans and mollusks capture for fishermen in the three of subdistrict. The purpose of this study was to determine levels of heavy metal lead (Pb) in fish, crustaceans and mollusks in the northern coast Bangkalan. The research activities include field observations and laboratory analysis in April-May 2013. Water and sediment sampling conducted at three locations in the waters of the North Coast Bangkalan include Klampis beach, Sepulu beach and Tanjung Bumi beach,, while samples of fish, crustaceans and mollusks in the capture of three fishermen in the district later in the analysis of lead content using Atomic Absorption Spectrophotometry (AAS) in BBLK (Center for Health Laboratory) Surabaya. The results showed that the average content of heavy metals of lead on puffer fish 0.043 ppm, on manyung fish 0.095 ppm, on white shrimp 0.103 ppm, on crab 0.113 ppm, squid and mussels 0.149 ppm 0.08 ppm. The content has not exceeded the threshold value set by the government (fish: 0.3 ppm; crustaceans :0.5 ppm and mollusks : 1.5 ppm) (SNI, 2009) so it is still safe for human consumption. The average content of heavy metals in sea water is 0.135 ppm and sediment is 0.746 ppm. The content exceeds the threshold value set by the government (water: 0.008 ppm and sediment: 0.07 ppm) (SNI, 2009) so that in the long term is harmful to marine life that exist in the northern waters of the sea water quality Bangkalan.Water quality parameters in the coastal waters of the North Sea Bangkalan still in normal condition as habitat for marine life. Water quality parameters are still in good condition for growth in aquatic biota. Temperature ranges from 28 - 31oC, pH ranges from 6-8, dissolved oxygen ranged between 4-6 ppm, salinity ranged range 25-35 ppm.